Optimalisasi Pembelajaran Kewirausahaan Bahasa dan Seni Melalui Integrasi Interactive Quiz Gamifikasi dalam Sistem Pembelajaran Jaringan - Abdul Rahman Prasetyo; Iriaji; Ike Ratnawati; Alby Aruna; Eka Putri Surya; Adinda Marcelliantika; Ginanjar Atma Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to optimize language and arts entrepreneurship learning by integrating gamified interactive quizzes in a network learning system. The research method involves the development and implementation of interactive quizzes that use gamification elements to increase student engagement and learning motivation. The research results show that the use of interactive quizzes with gamification elements can increase students' active participation, understanding of the material, and interest in language and arts entrepreneurship. The evaluation shows a significant increase in the achievement of learning outcomes and student satisfaction with the learning methods applied. The integration of technology in network learning proves its effectiveness in creating a more dynamic and interactive learning environment.